The WorldFish Experience with Impact Assessment - Rossignoli, Cristiano (WorldFish, 2024)
This presentation focuses on impact assessment, which measures changes attributed to specific interventions such as projects, programs, or policies. It aims to identify causal effects while distinguishing them from other influencing factors. Topics covered include the characterization of aquaculture systems in Bangladesh, challenges and limitations, GIFT Tilapia (Genetically Improved Farmed Tilapia), characterization methodology, alternative data and digital tools, and impact assessment.